Experimental Investigation on Heat Transfer and Pressure Drop Characteristics of Air Flow over a Staggered Flat Tube Bank in Crossflow - M., Ishak; Tahseen, Tahseen Ahmad; M. M., Rahman (Universiti Malaysia Pahang, 2013)
This paper presents an experimental investigation into the heat transfer and pressure drop characteristics of air flow in a staggered flat tube bank in crossflow with laminarforced convection. Measurements were conducted for sixteen tubes in the direction of flow and four tubes in rows. The air velocity varies between 0.6–1.0 m/s and the Reynolds number varied from 373 to 623. The total heat flux supplied in all tubes are changed from 967.92 to 3629.70 W/m2. The results indicate that the average Nusselt number for all the flat tubes increased by 11.46–46.42%, with the Reynolds numbers varying from 373 to 623 at the fixed heat flux. The average Nusselt number increased by 21.39–84%, and the total heat flux varyied between 967.92–3629.70 W/m2 with a constant Reynolds number Re = 498. In addition, the pressure drop decreased with an increase in the Reynolds number. A new mean Nusselt number-Reynolds number correlation was found, and the correlation yielded good predictions for the measured data with a confidence interval of 98.9%.